Agricultores familiares nas feiras livres goianienses: estudo de suas relações sociais, culturais e econômicas - Bittencourt, Blenda Domingues (2021)
The objective of Chapter II was to identify whether the category of family farmers, especially those who produce fruits, uses the marketing channel, such as open markets, to sell their production, without departing from the way of life and traditional forms of production. The research is qualitative, with descriptive quantitative aspects. He used an outlining procedure such as bibliographic, documentary and field research. Data collection took place with the application of a questionnaire and observation techniques, which took the form of a survey. As a result, it was possible to recognize the insertion of family farmers in this métier, it was concluded that they establish relationships in the social, cultural and economic dimensions; allowed to understand the functioning and dynamics of open markets and to identify their origin in the macro-region of the city of Goiânia/GO. The objective of Chapter III was to of this research was to search in the free markets in Goiânia/GO, the presence of family farmers, observing their specificities regarding the social, cultural and economic relations established in this environment and between the actors that compose it. To carry out this research, the questionnaires and semi-structured interview techniques were used as a method to collect data, the nature of this data is qualitative and quantitative and descriptive, the field research took place in the environment of all regularized free fairs in Goiás, among the September 2018 to March 2019. The collected data were refined using descriptive statistics. The results obtained clearly reveal the existence of a significant contingent of family farmers inserted in the free fairs in Goiás. The objective of Chapter IV this research was to search in the free markets in Goiânia/GO, the presence of family farmers, observing their specificities regarding the social, cultural and economic relations established in this environment and between the actors that compose it. To carry out this research, the questionnaires and semi-structured interview techniques were used as a method to collect data, the nature of this data is qualitative and quantitative and descriptive, the field research took place in the environment of all regularized free fairs in Goiás, among the September 2018 to March 2019. The collected data were refined using descriptive statistics. The results obtained clearly reveal the existence of a significant contingent of family farmers inserted in the free fairs in Goiás. The purpose of Chapter V was to verify the insertion of family farmers in the open markets in Goiânia/GO and their social, cultural and economic relations. It delimited the research, outlining qualitative and quantitative descriptive procedures. The results confirm the participation of family farmers in the fairs in Goiás, with social, economic and cultural relations between them and other actors. It is concluded in this way, that open markets represent a fertile field for family farming, being promising for rural and local development.